Patient experience surveys for endometriosis care: A scoping review - Jenny King; Caroline Killpack (Women's Health)
Background: Understanding experiences of care for endometriosis is an important source of evidence for supporting the improvement of care quality for this long-term condition. Patient-reported experience measures are a key tool for providing this insight. However, in England, there is no national survey of experiences of endometriosis care, making it difficult to understand where care is working well and how it can be improved. Objectives: This scoping review aimed to identify and describe existing surveys globally for measuring patient experience of care for people with endometriosis. Eligibility criteria: The population of interest included people with endometriosis. The concept was questionnaires in any format (e.g. article or web-based) exploring the experience of care for endometriosis in the context of any care setting. Sources of evidence: PubMed and ProQuest databases were searched between August and September 2024. Charting methods: Information extracted included study information (e.g. article title, authors, year of publication, research objectives, country), inclusion/exclusion criteria (e.g. population, concept, context) and patient experience measure characteristics (e.g. name of experience measure, number of questions, domains of person-centred care, survey mode and contact approach, development process). Results: Out of the 209 articles screened, only seven surveys were identified for inclusion in the review. These surveys varied in context, number of items, domains of care, survey mode and contact approach. Most of the surveys focussed narrowly on one aspect of care, such as diagnosis or inpatient treatment, and three surveys included only two questions related to patient experience. Only one survey, the ENDOCARE Questionnaire, covered all eight Picker Principles of Person-Centred Care. Conclusions: With only a small number of surveys identified and only one capturing all core aspects of person-centred care, there are limited resources available for those wishing to understand and improve care quality for people with endometriosis.